Canopy structure within a Quercus ilex forested watershed: variations due to location, phenological development, and water availability (Trees-Structure and Function, 1994)
Spatial and temporal changes in canopy structure were studied in 1988 and 1989 in a Mediterranean Q u e r c u s ilex forest in north-eastern Spain. Due to differences in precipitation patterns the 1989 growing season was drier than the 1988 growing season. Sampling was conducted in parallel at two sites which represent endpoints along a slope gradient within a watershed (ridge top at 975 m, and valley bottom at 700 m). At both sites, similar inter-annual changes in canopy structure were observed in response to differences in water availability. Samples harvested in the upper 50 cm of the canopy during 1989 exhibited a de- crease in both average leaf size and the ratio of young to old leaf and stem biomass relative to samples obtained in 1988. At the whole canopy level, a decrease in leaf pro- duction efficiency and an increase in the stem to leaf bio- mass ratio was observed in 1989. Temporal changes in canopy leaf area index (LAI) were not statistically sig- nificant. Average LAI values of Q. ilex at the two sites were not significantly different despite differences in tree stature and density (4.6 m 2 m -2 at the ridge top, and 5.3 m 2 m -2 at the valley bottom). Vertical distribution of leaves and stems within the canopy was very similar at the two locations, with more than 60% of the total LAI in the uppermost metre of the canopy. The possible significance of such an LAI distribution on the canopy carbon budget is discussed.